EMPLOYEE PERFORMANCE STUDY DEPARTMENT OF PUBLIC WORKS AND SPATIAL PLANNING BANJARNEGARA DISTRICT - Anna Probowati; Dewi Shanti Nugrahani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to determine the effect of simultaneously (simultaneously) or partially thevariables of motivation, discipline, compensation and work environment on the performance of the Public Works and Spatial Planning Office of Banjarnegara Regency. This research method uses descriptive quantitative research design. The population is employees who work in the Department of Public Works and Spatial Planning, Banjarnegara Regency, amounting to 198 people. The sampling technique used in this study was simple random sampling with a sample size of 81 respondents. Collecting data by using a questionnaire. The data analysis technique used is statistical analysis, namely multiple linear regression test, F test, t test, and the coefficient of determination. The results of the study indicate that motivation, discipline, compensation and work environment partially and significantly affect the performance of the Public Works and Spatial Planning Officers of Banjarnegara Regency. Suggestions from this research, employees of the Public Works and Spatial Planning Office of Banjarnegara Regency continue to improve motivation, discipline, compensation and the existing work environment, so that employee performance will increase and be better than before. Keywords: Performance, Motivation, Discipline, Compensation, Work Environment